Exploring activated carbon as an alternative to SBS in asphalt mixtures: Performance and fatigue analysis - Yalcin, Erkut; Ince, Ragip; Yilmaz, Mehmet (Elsevier, 2025)
Fatigue cracking in hot mix asphalt (HMA) is a critical issue in flexible pavement maintenance, often leading to premature failure. Traditional fatigue tests are time-consuming and require significant manual effort. To address these challenges, static tests like the monotonic semi-circular bending (SCB) test have become popular for evaluating asphalt mixture performance due to their simplicity in setup and specimen preparation. This study aimed to assess the mechanical properties of asphalt mixtures using both fatigue and SCB tests, focusing on mixtures with three different additives. The study compared the widely-used styrene-butadiene-styrene (SBS) additive with activated carbon additives derived from waste materials. Hot mix asphalt samples with two different notch depths were tested, and fracture parameters were evaluated using elastic-plastic fracture mechanics (EPFM) and linear elastic fracture mechanics (LEFM) techniques. The results indicated that both the fatigue and SCB tests produced similar outcomes, with the SBS mixture showing the best performance. It was observed that the maximum load and fracture toughness values decreased as the notch depth increased, with the highest fracture energy in asphalt mixtures obtained from the 3SBS mixture. Notably, the 2AC additive also showed potential as a viable alternative to SBS, offering comparable fracture performance. Data availability: Data will be made available upon reasonable request.
Keywords: Activated carbon; Hot mix asphalt; SBS; Fatigue; Semi-circular bending (SCB)